2010
DOI: 10.1332/030557309x462547
|View full text |Cite
|
Sign up to set email alerts
|

Local histories and local sensemaking: a case of policy implementation in the English National Health Service

Abstract: Central policies that are only loosely specified might be expected to result in local variations in interpretation and implementation, and practice-based commissioning in the English National Health Service (NHS) is no exception. We show how local ‘sensemaking’ in relation to this policy has been influenced by local histories and by conceptual schemata derived from earlier reorganisations of the NHS. Changes to organisational formalities do not necessarily, therefore, result in reappraisals of sensemaking on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…Whilst we did observe occasional examples of commissioners making such choices, it was notable that this only occurred at the margins, involving small volumes of straightforward elective care. What is striking is that these findings are strongly redolent of research findings from earlier phases of the NHS purchaser/provider split, in that formal changes in transaction rules are mediated through pre-existing social and institutional arrangements (Flynn et al, 1996;Ferlie, 1994;Hughes et al, 1997;Mays et al, 1998). In more abstract terms, commissioning has remained a relational (Powell, 1991) rather than an economic phenomenon, embedded (Granovetter, 1995) in existing social and institutional structures.…”
Section: Discussionmentioning
confidence: 75%
“…Whilst we did observe occasional examples of commissioners making such choices, it was notable that this only occurred at the margins, involving small volumes of straightforward elective care. What is striking is that these findings are strongly redolent of research findings from earlier phases of the NHS purchaser/provider split, in that formal changes in transaction rules are mediated through pre-existing social and institutional arrangements (Flynn et al, 1996;Ferlie, 1994;Hughes et al, 1997;Mays et al, 1998). In more abstract terms, commissioning has remained a relational (Powell, 1991) rather than an economic phenomenon, embedded (Granovetter, 1995) in existing social and institutional structures.…”
Section: Discussionmentioning
confidence: 75%
“…It builds on recent research examining the way that commissioning is understood and undertaken locally,5–7 the spaces in which commissioning takes place8 and the people involved 9 10. The focus is on the commissioning of services for people with long-term conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We found that PBC had made a good deal of progress, albeit with considerable local variation 13 and sometimes restrained by perceived organisational 'barriers'.…”
Section: Discussionmentioning
confidence: 89%